Incorporating Oxygen Uncoupling Kinetics into Computational Fluid Dynamic Simulations of a Chemical Looping System. Issue 10 (7th June 2016) - Hamilton, Matthew A.; Whitty, Kevin J.; Lighty, JoAnn S.
Abstract: Chemical looping with oxygen uncoupling (CLOU) is a carbon‐capture technology that utilizes a metal oxide as an oxygen carrier to separate oxygen from air and releases gaseous O2 into a reactor where fuel is fed. Earlier experimental and simulated work has been performed on systems less than 1 MW. Previous work has been limited to one‐dimensional kinetic simulations. Literature kinetics were modified to work in a Barracuda‐VR simulation package. A simplified spreadsheet model was used to verify the Barracuda‐VR simulation adaption of the kinetics to previously published results. The simulated kinetics, literature models, and raw data matched well. The adapted kinetics were then incorporated into a 10 kW dual bubbling bed CLOU system three‐dimensional simulation. The simulations predicted carbon capture efficiency similar to that reported previously for similar systems. The solid circulation rate, temperature profile, and gas concentration profiles followed the expected trends. The overall three‐dimensional simulation of kinetics showed reasonable results for what has been previously reported. Abstract : CLOU computing : A three‐dimensional CLOU reaction computational fluid dynamic simulation is developed for a 10 kW dual bubbling bed reactor. The kinetics are adjusted from published work to function in the simulation. These adjusted kinetics are verified and validated with previous published work. The carbon capture efficiency was 0.94, which is above the US DOE targeted efficiency of 0.90.